مساهمة الشبكة المعلوماتية في تحسين الأداء الوظيفي دراسة ميدانية بمؤسسة الصندوق الوطني للتامين عن البطالة ولاية سوق أهراس - سهيلي شريفة; بوجلال لبنى (My University, 2018)
Study Summary: The Internet is considered one of the most important modern technologies adopted by organizations today to improve the performance of their employees in particular, and the overall performance of the organization in general, in carrying out their various tasks. This is due to its positive impact, as well as the programs it provides that increase the effectiveness and efficiency of its employees at work. We attempted to identify the contribution of the Internet to improving job performance at the National Unemployment Insurance Fund. The research problem was addressed by posing the following main question: How does the Internet contribute to improving employee job performance? From this, the following questions branch out:  To what extent is the Internet used within the organization?  Has the use of the Internet led to improved job performance?  What are the obstacles facing the use of the Internet to improve job performance? In this study, we relied on the descriptive approach, a questionnaire, and a purposive sample of 66 individuals using the Internet. ----------------------- ملخص الدراسة: يُعتبر الإنترنت من أهم التقنيات الحديثة التي تتبناها المؤسسات اليوم لتحسين أداء موظفيها بشكل خاص، وأداء المؤسسة بشكل عام، في أداء مهامها المختلفة. ويعود ذلك إلى تأثيره الإيجابي، وما يقدمه من برامج تزيد من فعالية وكفاءة موظفيها في العمل. وقد سعينا إلى تحديد مدى مساهمة الإنترنت في تحسين الأداء الوظيفي في الصندوق الوطني للتأمين ضد البطالة. وتمثلت مشكلة البحث في طرح السؤال الرئيسي التالي: كيف يُسهم الإنترنت في تحسين الأداء الوظيفي للموظفين؟ ويتفرع منه الأسئلة التالية: إلى أي مدى يُستخدم الإنترنت داخل المؤسسة؟ هل أدى استخدام الإنترنت إلى تحسين الأداء الوظيفي؟ ما هي المعوقات التي تواجه استخدام الإنترنت لتحسين الأداء الوظيفي؟ وقد اعتمدنا في هذه الدراسة على المنهج الوصفي، واستبانة، وعينة قصدية قوامها 66 فردًا من مستخدمي الإنترنت.
Keywords: الشبكة المعلوماتية، الأداء الوظيفي، البطالة